Implementasi Keamanan Data Menggunakan Algoritma Rivest Code 4 (RC4) Pada Sistem Informasi Inventory Stock Barang Pada Distributor PT.Wings Food - Susanto, Susanto (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 2 Agustus 2017, 2017)
Rivest code 4 (RC4) is a cryptographic algorithm modern symentic key which has an operating mode stream chipper. It’s used two substitutions box in processing data and information, they are array with a permutation length of 256 and second s-box as permutation with has a function as public key. Algorithm rivest code 4 was used for data encryption, message or information.  Information system inventory stock of goods at distributor PT. Wings Food is a system that processed incoming and outgoing goods data, so that the data stored in database must be guaranteed confidential and its secur e . To keep the security of stock data items stored in database, it was combined with algorithm rivest code 4. Thus, the data encrypted in database would not be known the real meaning and was difficult to change or replaced. Symmetry key that was used for processing encryption and description rivest code 4 algorithm at information system inventory stock of goods in source code. Algorithm implementation rivest code 4 was made by programming language Hypertext Preprocessor and MySQL. Based on the result, the data displayed in database PT. Wings Food was encrypted, so it was found that the system could keep the data confidential in a secure. In short, the data displayed was unencrypted.